Philip Larkin and the Poetics of Resistance. Andrew Mckeown and Charles Holdefer, eds. Paris: L’Harmattan, 2006 - Blanco Uría, Hector (Estudios Ingleses de la Universidad Complutense, 2009)
Sin resumen